POLITENESS STRATEGIES IN DIGITAL POLITICAL COMMUNICATION: GANJAR PRANOWO’S INSTAGRAM INTERACTION - Marisa, Vera; Manugeren, M.; Suhadi, Jumino (JOURNAL OF LANGUAGE, 2025)
This study investigates the politeness strategies employed in interactions on Ganjar Pranowo's Instagram account, with particular attention to how linguistic choices shape digital political communication. It explores the strategies used by both followers and the politician to navigate social dynamics, express solidarity, and manage face-threatening acts within a public online setting. Utilizing a qualitative content analysis approach, the study examines 250 comments and responses, categorized according to Brown and Levinson’s four politeness strategies: bald-on-record, positive politeness, negative politeness, and off-record. The findings reveal that positive politeness is the most commonly employed strategy among followers, reflecting a supportive and affiliative communicative style. Bald-on-record strategies are also frequently observed, indicating direct and unmitigated expressions. In contrast, Ganjar Pranowo primarily adopts bald-on-record strategies, suggesting a preference for clarity and communicative efficiency. Negative politeness and off-record strategies appear less frequently, underscoring the overall informal and inclusive nature of the digital interactions.